<span><span>1. <span>x =(8-√76)/2=4-√ 19 = -0.359 </span>
</span><span> <span>
2. x =(8+√76)/2=4+√ 19 = 8.359 </span>
</span></span>
for the formula is
Y = starting population x (1-rate of change)^number of years
2010-2001 = 9
Y= 567 x (1-0.015)^9 = 494.89, round up to 495 people
Multiply the top one by 3 for x, so you can eliminate x and find y
then plug in the y into one of the equations to find x
Answer:
<em>Here</em><em> </em><em>is</em><em> </em><em>your</em><em> </em><em>answer </em><em>.</em><em> </em><em>Hope</em><em> </em><em>this</em><em> </em><em>helps</em><em> </em><em>you</em><em>.</em>